2023
DOI: 10.1002/cdt3.59
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy treatment patterns at hospital discharge and clinical outcomes among patients with heart failure with reduced ejection fraction

Abstract: Background: This study aimed to assess the prescribing patterns of evidencebased pharmacotherapy and their association with clinical outcomes in patients with heart failure with reduced ejection fraction (HFrEF) in Thailand. Methods: A retrospective cohort study of patients with HFrEF was conducted. Treatment with a β-blocker and renin-angiotensin system inhibitors (RASIs) with or without mineralocorticoid receptor antagonists (MRAs) at discharge was regarded as guideline-directed medical therapy (GDMT). All o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(129 reference statements)
1
1
0
Order By: Relevance
“…In agreement with our results, the ESC Heart Failure Long-Term Registry and the international cohort study by Lam et al also revealed age and blood pressure to be parameters significantly influencing mortality [40,56]. Triple therapy application not only influenced mortality but also independently reduced the risk of all-cause rehospitalisation at 1 year in our study, in accordance with the largest RCTs and international data [57,58].…”
Section: Predictors Of 1-year All-cause Mortality and All-cause Rehos...supporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our results, the ESC Heart Failure Long-Term Registry and the international cohort study by Lam et al also revealed age and blood pressure to be parameters significantly influencing mortality [40,56]. Triple therapy application not only influenced mortality but also independently reduced the risk of all-cause rehospitalisation at 1 year in our study, in accordance with the largest RCTs and international data [57,58].…”
Section: Predictors Of 1-year All-cause Mortality and All-cause Rehos...supporting
confidence: 93%
“…A total of 257 patients were involved in our retrospective analysis. A total of 74% of them were male, and the median age was 65 [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] years. A total of 40% of patients required hospitalisation for HF before the index event, 32% were newly diagnosed (de novo) HFrEF patients and 45% had at least partly ischaemic aetiology of HF.…”
Section: Patient Populationmentioning
confidence: 99%